Nazi hunger politics : a history of food in the Third Reich - Gerhard, Gesine 1999- (Rowman & Littlefield studies in food and gastronomy, 2015)
"Food played a central role in the Third Reich, to satisfy the daily needs of the people, to prepare Germany for war, to decrease the country's dependence on food imports and as the foundation of a racial ideology that justified the murder of millions of Jews, prisoners of war and Slavs. This book is the first to address the topic of food during the Nazi Reich in a comprehensive way. It illustrates the importance of food in Nazi ideology, its use as a justification for war and as a tool in the genocide of Jews, civilians and Soviet soldier"...Provided by publisher